2017
DOI: 10.1097/mpg.0000000000001324
|View full text |Cite
|
Sign up to set email alerts
|

Protein Malnutrition During Juvenile Age Increases Ileal and Colonic Permeability in Rats

Abstract: Protein malnutrition can lead to morphological and functional changes in jejunum and ileum, affecting permeability to luminal contents. Regarding the large intestine, data are scarce, especially at juvenile age. We investigated whether low-protein (LP) diet could modify ileal and colonic permeability and epithelial morphology in young rats. Isocaloric diets containing 26% (control diet) or 4% protein were given to male rats between postnatal days 40 and 60. LP-diet animals failed to gain weight and displayed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…In the present study, the combination of 3 weeks LP diet with chronic oral gavage of indomethacin significantly decreased Cldn2 and Ocln mRNA levels. These results are in accordance previous studies showing a reduced ileal and colonic occludin protein expression in protein-deprived rats 10,11 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, the combination of 3 weeks LP diet with chronic oral gavage of indomethacin significantly decreased Cldn2 and Ocln mRNA levels. These results are in accordance previous studies showing a reduced ileal and colonic occludin protein expression in protein-deprived rats 10,11 .…”
Section: Discussionsupporting
confidence: 94%
“…Dietary protein restriction is used from 0 to 7% of proteins and are associated with gut barrier dysfunction, only in the case of drastic dietary protein restriction 8 . Similarly, rats fed with LP diet (4% protein) for 20 days had growth retardation without effect on colonic or ileum permeability to macromolecules 10 . Brown et al study showed no impact of 3 weeks of LP diet (7%) in weaning mice on fecal calprotectin levels 9 while it increased intestinal permeability 9 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, tissue viability is a major concern and therefore incubation times no longer than 3 h are recommended (Clarke, 2009). The use of everted gut sacs to measure the transit of fluorescent probes has the advantage of not demanding specialized equipment, but larger amounts of tissue are required (3–4 cm 2 ) (Moyano-Porcile et al, 2015; Eyzaguirre-Velasquez et al, 2017). In the Ussing chamber, ion transport across the intestinal wall can be measured in very small segments of tissue (1 cm 2 ) but a more expensive setup is necessary.…”
Section: Methods For Testing Gut Permeability and Other Markers Of Bamentioning
confidence: 99%
“…Dietary and microbiota changes can protect the intestinal barrier function, which is the case for glutamine (Li et al, 1994), bacteria-derived lactic acid (Ren et al, 2018) and butyrate (Kelly et al, 2015). Other interventions disrupt the gut barrier, as in the case of DSS (Poritz et al, 2007), TNBS (Bregeon et al, 2016; Xu et al, 2018) or heavy metal supplementation (Zhai et al, 2016), low protein (Eyzaguirre-Velasquez et al, 2017) or high fat diet (Hamilton et al, 2015), infection (Guttman et al, 2006; Goossens et al, 2018) or CLP (Parida et al, 2015). These models can be considered to have good construct validity for organic diseases (i.e., those where morphological and/or biochemical features are altered) where barrier function is compromised.…”
Section: Studying Gut Barrier Alterations In Animal Modelsmentioning
confidence: 99%